Zintegrowany system informacyjno-analityczny w przedsiębiorstwie - Sierocki, Robert (Integrated Information-Analytical System in the Enterprise, 2005)
In the article model of integrated information-analytical system was proposed. It consists of 6 information and business layers. The model should be helpful to determine tools to integrate analytical systems.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1081, s. 231-239